2021
DOI: 10.3389/fncel.2020.627846
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgolide B Maintains Calcium Homeostasis in Hypoxic Hippocampal Neurons by Inhibiting Calcium Influx and Intracellular Calcium Release

Abstract: Ginkgolide B (GB), a terpene lactone and active ingredient of Ginkgo biloba, shows protective effects in neuronal cells subjected to hypoxia. We investigated whether GB might protect neurons from hypoxic injury through regulation of neuronal Ca2+ homeostasis. Primary hippocampal neurons subjected to chemical hypoxia (0.7 mM CoCl2) in vitro exhibited an increase in cytoplasmic Ca2+ (measured from the fluorescence of fluo-4), but this effect was significantly diminished by pre-treatment with 0.4 mM GB. Electroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Even though ER Ca 2+ depletion represents an undisputed factor of neuronal cell injury, the modulation of the STIM1/ORAI1 complex during ischemia is still under scrutiny. For instance, ORAI1 and STIM1 levels are significantly reduced in hypoxic cortical neurons [50], whereas STIM1 expression is elevated in hippocampal neurons exposed to chemically induced hypoxia [51]. We found that STIM1 levels remain unchanged after long-term incubation with Tg or in the absence of glucose, i.e., when ER is depleted and Ca 2+ entry is stimulated.…”
Section: Discussionmentioning
confidence: 60%
“…Even though ER Ca 2+ depletion represents an undisputed factor of neuronal cell injury, the modulation of the STIM1/ORAI1 complex during ischemia is still under scrutiny. For instance, ORAI1 and STIM1 levels are significantly reduced in hypoxic cortical neurons [50], whereas STIM1 expression is elevated in hippocampal neurons exposed to chemically induced hypoxia [51]. We found that STIM1 levels remain unchanged after long-term incubation with Tg or in the absence of glucose, i.e., when ER is depleted and Ca 2+ entry is stimulated.…”
Section: Discussionmentioning
confidence: 60%
“…LTCCs play a central role in calcium overload, and the regulation of LTCC activity is the focus of considerable research efforts. 53 The inhibition of LTCCs leads to a decrease in Ca 2+ entry, which in turn reduces harmful calcium overload, thereby protecting the heart against ischemic injury. Calcium ion blockers are the most common and widely used drugs for the treatment of MI.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, CAR has the potential to be an effective therapeutic agent for IS. In 2021, Li et al found that injection of Ginkgolide B (GB) , the active ingredient of terpene lactones ( Wang et al, 2020 ), in an animal model of AD reversed the levels of TFR1 and NOCA4 and upregulated the expression of Nrf2 and GPX4 in the brains of SAMP8 mice, which exhibited neuroprotective effects in AD mice ( HĂ©bert et al, 2022 ).…”
Section: Small Molecule Ferroptosis Inhibitorsmentioning
confidence: 99%